How to design a life worth smiling about : developing success in business and in life - Davis, Darryl (Darryl D.) (McGraw Hill professional., 2014)
"Bestselling author Darryl Davis helps you meet any challenge with a positive outlook--and provides scientifically proven reasons why this generates very real business benefits. Being happy isn't just about being happy--it's about physical, mental, and financial gain. Davis gives you the tools you need to overcome negativity and make vast improvements to your career and personal life. He provides practical mental tools for managing stress, dealing with difficult personalities, self motivation, and overcoming rejection. Darryl Davis is a renowned real estate agent, broker, and speaker, and the creator of the real estate industry's top-selling training programs. He is the founder of the only year-long real estate coaching program, The POWER Program, which has proven results of agents doubling their income over their previous year, and is the creator of the nationally acclaimed 3-Day program, S.U.R.E. Results."--